Respuesta :

Answer:

A

Step-by-step explanation:

Given

2k² - k - 3

Consider the factors of the product of the k² term and the constant term which sum to give the coefficient of the k- term.

product = 2 × - 3 = - 6 and sum = - 1

The factors are + 2 and - 3

Use these factors to split the k- term

2k² + 2k - 3k - 3 ( factor the first/second and third/fourth terms )

= 2k(k + 1) - 3(k + 1) ← factor out (k + 1) from each term

= (2k - 3)(k + 1) → A

ACCESS MORE
EDU ACCESS
Universidad de Mexico